A noninvasive accelerated quantitative MR technique to distinguish drug resistance in prolactinomas: Early results - Rong Lu; Tingfang Hwang; Kaibo Tang; Qing Li; Caixia Fu; Ying-Hua Chu; Shangxuan Shi; Tobias Kober; Tom Hibert; Bin Lu; Yiming Li; Yao Lu; et al. (Biomedical Technology)
Management of dopamine agonist (DA) resistance in prolactinoma (PRLoma) remains challenging due to the lack of detecting approach and reliable imaging marker. In this cross-sectional study, PRLoma patients were recruited prospectively from a single-center outpatient clinic from May 2024 to September 2024. A noninvasive accelerated quantitative MR technique (GRAPPATINI, GeneRalized Autocalibrating Partially Parallel Acquisitions acceleraTed T2 mappINg) was applied to investigate the correlation between quantitative T2 values and DA resistance. The T2 values of tumors with multiple echo times (TEs) and signal intensity (SI) ratios were analyzed. A total of 30 participants were included, of which 20 were DA-sensitive and 10 were DA-resistant. The T2 values were significantly lower in DA-resistant PRLoma than those in DA-sensitive PRLoma (76.85 ​± ​29.84 ​ms vs 135.88 ​± ​69.86 ​ms, P ​= ​0.0048), whereas the T2 SI ratio revealed no significant difference. The area under the curve (AUC) of T2 values and T2 SI ratio for distinguishing DA sensitivity were 0.850 and 0.668, respectively. The ratio distributions at different TEs (TE10 ​ms, TE38 ​ms, TE42 ​ms, TE55 ​ms, and TE90 ​ms) were significantly different at TE38 ​ms (P ​= ​0.026) between two groups. The AUC of T2 values and TEs for DA sensitivity in PRLoma were 0.850 (T2map), 0.680 (TE10 ​ms), 0.730 (TE38 ​ms), 0.690 (TE42 ​ms), 0.520 (TE55 ​ms), and 0.670 (TE90 ​ms), respectively (P ​= ​0.0107). These findings highlight the translational potential of T2 values as a promising imaging biomarker for evaluating DA resistance in PRLoma.